Physical oceanography during the cruise Hai Yang Di Zhi Shi Hao in South China Sea in September 2018, station SCS-36 - Joanna J Waniek; Helena C Frazão; Ingo Schuffenhauer; Robert Mars (PANGAEA, 2021)
This set provides 68 CTD profiles of temperature, conductivity, dissolved oxygen, fluorescence, turbidity, Surface Photosynthetically Active Radiation (SPAR) and sound velocity measured on board the Chinese R/V Hai Yang Di Zhi Shi Hao in September 2018, in the northern South China Sea, within the project Megacity extquotesingles fingerprint in Chinese marginal seas: Investigation of pollutant fingerprints and dispersal. Additionally, oxygen saturation, salinity, potential temperature and potential density are also provided. The dataset was used to study the presence and spatial distribution of natural and synthetic estrogenic compounds and pharmaceutical and personal care products (PPCPs) in the Pearl River Estuary and northern shelf of the South China Sea.
In: Waniek, JJ et al. (2021): Physical oceanography during the cruise Hai Yang Di Zhi Shi Hao in South China Sea in September 2018 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.936352